Riding the Digital Wave of Exercise, Health, and Sports Training Optimization - Rodrigo Zacca; Flávio Antônio de Souza Castro; Rui M. S. Azevedo (MDPI AG, 2024)
The digital era is opening countless possibilities in "Sport Sciences"; "Public, Environmental, and Occupational Health"; and "Physical Therapy, Sports Therapy, and Rehabilitation" areas [...]